2021
DOI: 10.1111/jtxs.12631
|View full text |Cite
|
Sign up to set email alerts
|

Textural properties and muscle activities during mastication of normal and ultrasonically softened sticky rice aimed for consumers with swallowing disorder: A pilot study

Abstract: Ultrasonication was used to develop softer sticky rice for elder adults. Textural properties of original sticky rice (oSR) and ultrasonically modified sticky rice (mSR) were determined. In addition, jaw muscle activities during mastication of both oSR and mSR were investigated. Twenty‐seven healthy elderly subjects, age 68.9 ± 7.6 years, were asked to masticate both types of sticky rice in random sequence for three times with a 5‐min rest between each test. Activities of bilateral masseter and suprahyoid muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, the softening effect of blueberry texture after the pulsed electric field treatment was observed by Jin et al [27], however, they pay more attention to the microbial inactivation effect of the treatment. Pattra et al [31] have shown that ultrasound can effectively soften the sticky rice, making it more suitable for people with reduced chewing ability. Nowak et al [32] reported that the combination of freeze-thawing and ultrasonic treatment can significantly lower the hardness and chewiness of blueberries.…”
Section: Traditional Dietary Softening Approachesmentioning
confidence: 99%
“…For example, the softening effect of blueberry texture after the pulsed electric field treatment was observed by Jin et al [27], however, they pay more attention to the microbial inactivation effect of the treatment. Pattra et al [31] have shown that ultrasound can effectively soften the sticky rice, making it more suitable for people with reduced chewing ability. Nowak et al [32] reported that the combination of freeze-thawing and ultrasonic treatment can significantly lower the hardness and chewiness of blueberries.…”
Section: Traditional Dietary Softening Approachesmentioning
confidence: 99%
“…In organizing this special issue, our main consideration has been on the fundamental principles and feasible techniques of texture modification for adult dysphagia. For this purpose, a number of leading scientists have been approached for a contribution in topics including the effect of bolus rheology of texture-modified foods on the degree of modification (Stading, 2021a); relationship between masticatory variables and bolus characteristics of meat with different textures (Pematilleke, Kaur, Adhikari, & Torley, 2021); textural properties and muscle activities during mastication of normal and ultrasonically softened sticky rice (Wattanapan, Saengnil, Niamnuy, Paphangkorakit, & Devahastin, 2021); extensional rheology and tribology of polysaccharide solution (Funami & Nakauma, 2021); the physical properties of texture-modified foods (Stading, 2021b); the effect of the rheological properties of thickened fluids on the in vitro swallowing of solid oral dosage forms (Lavoisier, Shreeram, Jedwab, & Ramaioli, 2021); and microwave treatment to modify textural properties of high-protein gel applicable as dysphagia food (Pure, Yarmand, Farhoodi, & Adedeji, 2021).…”
mentioning
confidence: 99%